MANAJEMEN HUBUNGAN MASYARAKAT DALAM MENINGKATKAN CITRA PONDOK PESANTREN PERMATA NUSANTARA MADANI - Willa Septinilia; Ali Marzuki Zebua (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze public relations (PR) management in enhancing the image of Permata Nusantara Madani Islamic Boarding School amid the transition of its funding system from free to fee-based. The study employs a descriptive qualitative approach through in-depth interviews, observation, and documentation involving school leaders, PR officers, parents, and students. Data analysis was conducted through data reduction, data display, and conclusion drawing to obtain a comprehensive understanding. The results indicate that the success of PR is supported by three main aspects: core knowledge, shared expectations, and participatory culture. Core knowledge is reflected in the ability to understand internal and external conditions and to manage communication risks strategically and systematically, while shared expectations are evident in the alignment between leadership and PR in delivering policy messages consistently, clearly, and persuasively to the public. Participatory culture is manifested through open, dialogic, and responsive communication with parents and the wider community, supported by persuasive approaches based on trust, transparency, and accountability. The findings show that the change in the funding system does not diminish the institution’s image; instead, it enhances public trust, as indicated by the increasing number of students and community support.